Exploring the Role of Psychobiotics in Mental and Emotional Well-being and How Psychobiotics Can Help Fight Anxiety and Depression - Imran, Amna; Faisal, Fiza; Huda, Noor-Ul-; Jameel, Amna; Aslam, Rimsha; Jabbar, Isra (Indus Journal of Bioscience Research, 2025)
Human health relies heavily on gut microbiota because this microbe system affects both brain function and behavior while influencing the stress response mechanism through the microbiota-gut-brain axis. Probiotics and their specific type psychobiotics develop as innovative treatments which help individuals manage mental health conditions along with CNS diseases and treat depression and anxiety symptoms. A sufficient consumption of psychobiotics as live organisms offers mental health benefits by allowing them to engage with gut microbiota for controlling neurotransmitter synthesis and immune responses together with inflammation regulation. The current studies demonstrate how probiotics and prebiotics generate beneficial results which enhance mind performance and stress reduction and improve mood. This review reviews the influence of psychobiotics on neuron connections between the gut and brain through studies about how they affect serotonin and dopamine neural pathways and immune responses and their health benefits within fermented foods. The gut microbiota plays a crucial role in overall health by influencing brain function, mood, and stress responses through the microbiota-gut-brain axis. Probiotics and prebiotics help maintain a balanced gut microbiome, supporting mental performance, emotional stability, and immune function. Research links gut dysbiosis to various health disorders, highlighting probiotic foods like yogurt and kefir as potential treatments for anxiety, depression, and irritable bowel syndrome. Beneficial microorganisms such as Lactobacillus, Bifidobacterium, and Saccharomyces boulardii improve gut health. Advancing psychobiotics research will enhance mental healthcare strategies, offering innovative solutions for global health challenges and overall well-being.